People's courts and people's justice : a critical review of the current state of knowledge of people's courts, with a particular focus on South Africa - Moses, Joey (Centre for Law and Society, 2026)
This dissertation is an attempt at broadening the understanding of People's Courts and People's Justice in South Africa. People's Courts mushroomed throughout African townships in South Africa, especially during 1985/1886 to the extent J' that it was said to be a conspiracy, instigated by the then banned African National Congress (ANC) in alliance with the South African Communist Party (SACP), to overthrow the South African State. The central argument of this dissertation is that People's Courts, with its objective of creating a new legality which is encapsulated in the notion of People's Justice, did indeed shake the foundations of ·the Apartheidstate. It presented the white ruling bloc in South Africa with one of its biggest hegemonic challenges in the 1980s. People's Courts are dealt with in three parts. The first part explores the relationship between law, ideology and the state; the second explores that relationship within the South~African context, and th~ third locates people's courts within that context. In the latter part the continuities between People's Courts and the Makgotla are explored as well as the fundamental differences which exist between them, which differences also account for the different state strategies toward them. A comparative analysis of People's Courts in the different regions in South Africa indicates that the vast majority of these popular tribunals were not only deliberately anti-state. Apart from their immediate objectives of controlling crime in townships and reconciling parties to disputes, they also deliberately alligned themselves with the broader political movement which attempted to overthrow organs of state power and replace it with organs of people's power: the main objective being the realisation of people's power. The comparative analysis also reveals certain potential and real dangers as well as tensions within the operation of people's courts and in its alliance with the broader, extra-state political movement, which are reflected on in the conclusion.